The genus Mimogonia (Coleoptera: Staphylinidae: Osoriinae) from the Neotropical region with descriptions of four new species - Irmler, Ulrich (Zootaxa, 2007)
Four new species of the rove beetle genus Mimogonia Coiffait, 1978 are described from South America, Mimogonia hermani, Mimogonia hanagarthi, Mimogonia adisi, and Mimogonia huggerti. The new species were collected in the Amazonian regions of Peru or Bolivia and the state Amazonas in Brazil. Additional records are published of M. similis from Iquitos (Peru) and M. subopaca from Puerto Maldonado (Peru). A key to the Neotropical species of the genus is given.